Characteristics of home care for poststroke patients from the perspective of a physiotherapist - Bendová, Markéta; Vacková, Jitka; Míková, Marcela; Kuželková, Anna (Journal of nursing, social studies and public health, 2024)
Team neurorehabilitation care after a cerebrovascular accident (CVA/ stroke) in acute and inpatient facilities is at a very high level. However, models suitable for subsequent rehabilitation in home environments are less known. A review of the literature published between 2013–2023 was conducted using the PRISMA methodology. The search for relevant articles used three electronic databases, i.e., Web of Science, Scopus, and PubMed. Twenty-three articles were initially selected for review. This study summarizes the physiotherapeutic methods and approaches available to stroke patients undergoing rehabilitation in the home environment. The study also characterizes home rehabilitation programs in terms of content, duration, frequency of visits, availability, and use of self-therapy materials, interactions with the therapist, exercise record keeping, tools used to assess the functional status of stroke patients, and whether or what kind of an interprofessional team was involved in home rehabilitation. The goal of successful community rehabilitation is to have an interprofessional neurorehabilitation program specific to each stroke patient, and a program focused on the patient’s current needs and goals relative to their rehabilitation environment.